Ludwika Ostrowska – dzieciństwo i edukacja młodej dziedziczki z Maluszyna - Studnicka-Mariańczyk, Karolina (Biuletyn Historii Wychowania, 2014)
Ostrowska Ludwika was born September 5, 1851, in the palace of Maluszyn. Her father was Count Alexander Ostrowski of the house of Korab (1810–1896), her mother – Helena Countess of Morsztyns of the house of Leliwa (1815–1892). The countess was the youngest, sixth child of Alexander and Helen. The family environment exerted a significant influence on the development of Ludwika as a child, and later shaped her attitude in life. The childhood of the little countess passed in the happy atmosphere of the family home, under the watchful eye of her mother and carers, teachers and educators. In later years, as she grew older, Ludwika gradually took over the duties lady of the house and the management of a farm cottage and garden. She was also interested in social affairs, which was reflected in her commitment to charity.